African cashew nut producers rally together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
African cashew nut producers are worried about the new phytosanitary standards for food products imported into the EU that came into force in January 2005.